Documentation procedure in oral tradition - Abu Bakar, Roslina; Othman, Mohd Sukki; Makmun, Rozaiman; Abdul Razak, Nur Mimi Izzaty (Human Resources Management Academic Research Society (HRMARS), 2024)
Oral tradition is the heritage property of a collective. Therefore, the study of oral tradition or folk literature should be preserved in today's society in order to remain contemporary. It also needs to be implemented, especially when the world community is facing an era of globalization. Nevertheless, the documentation procedure for oral tradition materials is not an easy process. There are various constraints related to collecting and keeping collections of oral tradition materials. There are procedures and methods that need to be implemented so that oral traditions inherited from previous generations are not lost by the current modernization. It is well known that oral tradition is conveyed to the audience or community by oral speakers known as comforters or storytellers. There are various versions of oral traditions that are passed down from generation to generation as a means of entertaining and indirectly educating. The study of oral tradition or folk literature does not only require the content of the material but also the form, language, structure, motif, or all the elements found in the material. This writing has two objectives. Firstly, to identify the specifications of the oral tradition documentation procedure, and secondly, to produce a report on the documentation of the oral tradition. To achieve the objective of the study, this writing applies field and library methods.